Gastric Cancer in Young Patients - Dhobi, Manzoor A.; Wani, Khursheed Alam; Parray, Fazl Qadir; Wani, Rouf A.; Wani, Mohd Lateef; Peer, G. Q.; Abdullah, Safiya; Wani, Imtiyaz A.; Wani, Muneer A.; Shah, Mubashir A.; Thakur, Natasha (International Journal of Surgical Oncology, 2013)
Aim. The aim of this study was to see the clinical, pathological, and demographic profile of young patients with stomach carcinoma besides association with p53. Patients and Methods. Prospective study of young patients with stomach carcinoma from January 2005 to December 2009. A total of 50 patients with age less than 40 years were studied. Results. Male female ratio was 1 : 1.08 in young patients and 2.5 : 1 in older patients. A positive family history of stomach cancer in the first degree relatives was present in 10% of young patients. Resection was possible only in 50% young patients. 26% young patients underwent only palliative gastrojejunostomy. The most common operation was lower partial gastrectomy in 68%. Amongst the intraoperative findings peritoneal metastasis was seen in 17.4% in young patients. 50% young patients presented in stage IV as per AJCC classification (P value .004; sig.). None of the patients presented as stage 1 disease in young group. Conclusion. Early detection of stomach carcinoma is very important in all patients but in young patients it is of paramount importance.